A uridine diphosphate-glycosyltransferase GFUGT88A1 derived from edible mushroom Grifola frondosa extends oligosaccharide chains. (January 2022) - Liang, Ying-Ying; Zan, Xin-Yi; Sun, Lei; Fu, Xin; Cui, Feng-Jie; Tan, Ming; Shao, Ze-Yu; Sun, Wen-Jing
Graphical abstract: Highlights: A 51.7-kDa UDP-glycosyltransferase GFUGT88A1 in G. frondosa was heterologously expressed for the first time. GFUGT88A1 showed an activity to extend oligosaccharide chains. GFUGT88A1 preferred higher DP of oligosaccharides (>6) as acceptor. Recombinant GFUGT88A1 had optimum reaction temperature and pH of 37 ℃ and 7.0. Active sites of GFUGT88A1 bound with donor/acceptor mainly through hydrogen bonds. Abstract: Fungal glucans play a key role to provide energy, support cell structure, and present biological functions. However, the biosynthetic machineries of fungal glucan chains remain to be elucidated. Hence, we aimed to elucidate the biochemical and catalytic characteristics of a novel glucan synthesis-associated enzyme uridine diphosphate (UDP)-glycosyltransferase GFUGT88A1 derived from Grifola frondosa and predict its potential catalytic mechanism. The purified recombinant GFUGT88A1 had a molecular weight of 51.7 kDa with an optimum temperature of 37 °C and pH of 7.0. GFUGT88A1 showed preference for oligosaccharides with relatively higher polymerization degrees (≥6) as acceptors to extend its chain when using UDP-glucose as a donor. Molecular modeling and docking of GFUGT88A1 with donor UDP-glucose, and acceptors laminaribiose, laminarihexaose, and laminarinonaose indicated that the predicted amino acid residues at the active sites may bind the donor/acceptor protein primarily via hydrogen bonds with various binding energy values. The present study revealed that GFUGT88A1 extended glucan chains, which provides a reference to understand the biosynthesis pathway of mushroom glucans.